PS 14-10 GENDER-RELATED DIFFERENCES OF PATIENTS ARTERIAL HYPERTENSION WITH HEART FAILURE. RESULTS OF RUSSIAN REGISTER OF HEART FAILURE. (September 2016) - Lazareva, Natalia; Oshchepkova, Elena; Tereshchenko, Sergey
Abstract : Objective: Explore the clinical characteristics according to the gender of patients with heart failure in terms of etiology, comorbidity and treatment, included in the register. Design and Method: We employed data from the Russian Register of Heart failure n = 6465 of patients with heart failure (mean age 64, 5 ± 6, 9 years), I-IY functional class, (NYHA), who had medical examination and treatment in 2 policlinics, 4 cardiologic dispensaries and 5 urban hospitals selected at random during the study for the period 2010–2012. Results: Men with heart failure accounted for 58% (n = 3774), and women accounted for 42% (n = 2691). The women were older than the men 67, 6 ± 7, 1 years, and 62, 3 ± 6, 8 years (р < 0, 01) respectively and there was prevalence of arterial hypertension, the anamnesis TIA, stroke, chronic kidney disease, atrial fibrillation and preserved left ventricle ejection fraction (p < 0, 01). The women at the time of the survey, had significantly higher SBP - 142, 2 ± 14, 7 mmHg and 135, 4 ± 13, 03 in men (p < 0.01). There was a predominance of myocardial infarction, chronic obstructive pulmonary diseases in the men's medical history. They were treated equally with beta-blockers, ACEIs and/or ARBs regardless of sex. Conclusions: HF in women occurs at later age and with different comorbidites. There was arterial hypertension, SBP was significantly higher, at the medical history TIA, stroke; chronic kidney disease, atrial fibrillation and preserved left ventricle ejection fraction. On the other hand, men had the disease history of coronary artery disease and there was a prevalence of myocardial infarction.